Profiling vocabulary for proficiency development: Effects of input and general frequencies on L2 learning. (December 2019) - Sakata, Naoki
Abstract: Research in recent decades has suggested that high-frequency words should be prioritized in the learning of foreign language vocabulary. However, lexical frequencies in textbooks, which are often the most familiar learning material for learners, have been reported to differ somewhat from those in general corpora. To clarify the effects of these two different frequencies, this study examined the relationships among Japanese English as a foreign language (EFL) learners' vocabulary sizes, textbook frequency influence, and proficiencies to explore what type of vocabulary—in terms of textbook and general frequencies—leads to higher proficiency in foreign language learning. The results showed that words that are generally frequent but rarely occurring in textbooks contribute significantly to proficiency development and that those words distinguish learners with similar size vocabularies but different proficiencies. Based on the results, implications for research and language teaching are discussed.